Activated carbons derived from oil palm empty-fruit bunches: Application to environmental problems - Alam, Md. Zahangir; Muyibi, Suleyman Aremu; Mansor, M F; Wahid, R (JOURNAL OF ENVIRONMENTAL SCIENCES-CHINA, 2007)
Activated carbons derived from oil palm empty fruit bunches (EFB) were investigated to find the suitability of its application for removal of phenol in aqueous solution through adsorption process. Two types of activation namely; thermal activation at 300,500 and 800°C and physical activation at 150°C (boiling treatment) were used for the production of the activated carbons. A control (untreated EFB) was used to compare the adsorption capacity of the activated carbons produced from these processes. The results indicated that the activated carbon derived at the temperature of 800°C showed maximum absorption capacity in the aqueous solution of phenol. Batch adsorption studies showed an equilibrium time of 6 h for the activated carbon at 800°C. It was observed that the adsorption capacity was higher at lower values of pH (2-3) and higher value of initial concentration of phenol (200-300 m a ) . The equilibrium data fitted better with the Freundlich adsorption isotherm compared to the Langmuir. Kinetic studies of phenol adsorption onto activated carbons were also studied to evaluate the adsorption rate. The estimated cost for production of activated carbon from EFB was shown in lower price (USD 0.50/kg of activated carbon) compared the activated carbon from other sources and processes.